1901 Va. Acts 203, Extra Session, ch. 189, § 13. - (:unkn) unknown (My University, 1901)
The council shall have, subject to the provisions of this act, the control and management of the fiscal and municipal affairs of the town; of all property, real and personal, belonging to said town; and may make such ordinances, orders, and by-laws and regulations as it may deem necessary to carry out the following powers, which are hereby conferred on it . . . to regulate or prevent the storing of gunpowder
Keywords: GUNPOWDER - STORAGE